Relationship Between Level of Knowledge, Attitude and Motivation of Breast Self Examination (BSE) - Suchi Avnalurini Sharief; Wa Ode Marhani (Aloha International Journal of Health Advancement (AIJHA), 2018)
Breast cancer is one of the leading causes of death caused by cancer in women. Breast cancer (carcinoma mammae) is a condition in which cells have lost control and normal mechanisms, resulting in abnormal growth, rapid and uncontrolled that occurs in breast tissue. The only effective way to detect breast cancer early to date is only to detect as early as possible on the possibility of this disease, namely by doing Breast Self-Examination (BSE). This action is very important because almost 85% of breast lumps are found by the sufferers themselves. The purpose of this study was to determine the relationship between the level of knowledge, attitudes and motivation towards breast self-examination (BSE) in high school 9 Makassar students. This type of research was observational research with a cross sectional approach, using a sample of 182 class XI and XII students. The results of this study indicate there was no relationship between the level of knowledge of students with breast self-examination (BSE) (p-value = 0.065), there was a relationship between the attitude of students with breast self-examination (BSE) (p-value = 0.000) and there was a relationship between student motivation with breast self-examination (BSE) (p-value = 0.000). In conclusion, there is a relationship between students' attitudes and motivation towards breast self-examination (BSE) and there is no relationship between the level of knowledge of students and breast self-examination (BSE). Keywords: knowledge; attitude; motivation; BSE